UWE-KARSTEN HEYE, Los Benjamin. Una familia alemana, Trotta, Madrid, 2020 - Magaldi Fernandez, Adrian (Brocar. Cuadernos de Investigación Histórica, 2020)
UWE-KARSTEN HEYE, Los Benjamin. Una familia alemana, Trotta, Madrid, 2020.